Constructing the Validity of a Reading Assessment Model for 21st Century Education with a Focus on Self-Directed Learning - Yulmiati; Purba, Andiopenta; Harisnawati; Akhyaruddin; Adrias, Adrias; Nazhifah; Yulastri, Weni (Jurnal Arbitrer, 2025)
The purpose of this study is to validate a theoretically based blended assessment model with SDL and to show empirical validation of it. The study materials developed include a Model Book, a Students’ Book, and a Lecturer’s Book modeled on an authentic blended assessment framework for Basic Reading. A mixed-methods approach was used, and the validation process involved six expert validators. one-on-one evaluations were conducted with ten students and one lecturer who were purposively selected to be part of the study. The data were collected from validation sheets as well as semi-structured interviews. The results of statistical analysis performed on expert validation showed that the evaluation model has achieved high validity (i.e., content, construct, criteria, and face validity), producing a highly valid prototype of instruction. The findings indicate that there is no need for any further refinements,  and the model is thus ready for immediate implementation. Moreover, the intrinsic and impact validity of the authentic blended assessment model was corroborated with the support of empirical user validation (lecturer and students) feedback. This describes the inherent characteristics that include main usability elements like clarity, easy usage, logical mapping, and completeness of learning content. The impact aspect highlights the effectiveness and worthiness of using the products in real-world learning environments. The study addresses an important gap in reading assessment and presents a practical and effective solution for educators and institutions looking to leverage Basic Reading assessor skills within a Self-Directed Learning principles approach. The results can provide an important link to promote autonomous learning, develop evaluation methods, and, finally, enhance students’ independent learning ability and academic achievement.